Territorial economic intelligence: could Africa be the best choice for a regional economic integration strategy for Morocco? - (:unkn) unknown (My University, 2025)
This article explores the crucial role of economic intelligence (EI) as a catalyst for territorial integration and regional growth. It emphasizes that EI, through the collection and analysis of strategic information, enables economic players to make informed decisions in a constantly changing environment. Regional integration, on the other hand, fosters cooperation between neighboring countries to stimulate growth and reinforce political and social stability. The articulation between these two concepts is essential, as EI offers tools for understanding regional dynamics, while regional integration creates a framework conducive to exploiting this information. The article also highlights the historical evolution of EI, its fundamental practices, and its impacton corporate competitiveness, emphasizing the need to protect strategic information and manage risks. The latter is illustrated by the case of Morocco, which is asserting itself as a key player on the African scene, promoting strategies of integration andeconomic cooperation across Africa.
Keywords: African Research